ANALYSIS OF THE EFFECT OF INTERNAL CORPORATE GOVERNANCE ON AUDIT DELAY (A STUDY ON CONVENTIONAL BANK COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2017-2021) - Muhammad Nicko Fabriano; Imam Ghozali (Diponegoro Journal of Accounting, 2023)
This research aims to analyze the influence of internal Corporate Governance on audit delays in commercial bank companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The independent variables used are Board size (BOD), Independent Commissioner (IC), Audit Committee (AC), BOD Meet (BODM), Audit Committee Meet (ACM) and the dependent variable is audit delay.This research uses secondary data obtained from the annual reports of banking companies listed on the Indonesia Stock Exchange (BEI) during the 2017-2021 period. The number of samples used was 34 banking companies after purposive sampling was carried out, resulting in a total of 170 observations. This research uses the multiple linear regression method with the IBM SPSS 26 program which consists of the classic assumption test, f statistical test, t statistical test, and coefficient of determination test (R2). During the observation period, it shows that the data in this study have passed the classical assumption test. This shows that the data used meets the requirements for using a multiple linear regression equation model.The results of this study show that independent commissioners have a significant positive effect on ARL. Board Size (BOD) and Audit Committee Meetings (ACM) have a significant negative effect on ARL. Meanwhile, the audit committee (AC) and BOD meeting (BODM) have no effect on ARL.